PERKEMBANGAN BIOPSIKOSOSIOSPIRITUAL PESERTA DIDIK - Muh. Rodhi Zamzami (Ta`Limuna: Jurnal Pendidikan Islam, 2015)
The success of a teacher is closely related to the ability in comprehending the students’ growth and their development. Whilst, student development that was defined as a gradual progressive measured and coherent changes becomes one important thing psychologically stresses on comprehension of the basic process and dynamic behavior of the student. If not, trouble with education can’t be avoided as misdirection and disorientation. Hence, Islamic education seeks to integrate the student development that covers the whole biopsikososiospriritual. The effort is to guide and develop their potency as of they will be able to present the ilahiah values. This article regards the student dimension development as a holistic process in hope that learning can be carried out effectively.